Injectable Hierarchical Bioactive Hydrogels with Fibroblast Growth Factor 21/Edaravone/Caffeic Acid Asynchronous Delivery for Treating Parkinson's Disease - Junpeng Xu; Peng Dai; Chen Zhang; Na Dong; Caiyan Li; Chonghui Tang; Zhihao Jin; Shih‐Ho Lin; Luyang Ye; Tianmiao Sun; Yukai Jin; Fenzan Wu; et al. (Advanced Science)
Abstract Parkinson's disease (PD) is one of the most common long‐term neurodegenerative disorders, with multiple comorbid psychiatric and behavioral abnormalities. The combination of clinical drugs targeting different symptoms with smart hydrogels to achieve asynchronous releases is highly translational and challenging. Here, a hierarchical bioactive hydrogel (OACDP) is designed with asynchronous release based on PD pathology. The hydrogel with caffeic acid‐grafted polymer main chain is crosslinked using a micellar nanocrosslinker, with sufficient modulus (≈167 Pa), antioxidant activity (> 50%), injectability (30‐gauge syringe needle), and shape‐adaptability. Each of the three drugs (caffeic acid, fibroblast growth factor 21, and Edaravone) is separately engaged in different micro‐ or nanostructures of the hydrogel and released with asynchronous kinetics of first‐order release, zero‐order release, or matching Korsmeyer–Peppas model. The triple‐loaded hydrogel is injected into the brains of PD rats, showing behavioral improvement. Histological analysis revealed that the triple‐loaded OACDP hydrogels are effective in achieving immediate neuroprotection, i.e., reduction the loss of tyrosine hydroxylase in substantia nigra compacta and striatum (retained ≈10‐fold versus control), decreasing oxidative stress, reducing astrocyte and microglia activation, and stimulating the AMPK/PGC‐1α axis to regulate the mitochondrial function, providing a multi‐dimensional PD therapy. The asynchronous release of OACDP hydrogel provides a new conception for PD treatment and other neurodegenerative diseases.